Influencia de la retroalimentación reflexiva en el desarrollo de habilidades del pensamiento crítico en estudiantes de la Escuela de Negocios Internacionales y Turismo de la Universidad Nacional de la Amazonía Peruana Iquitos 2024 - Pasquel Chong, Hedmer Antonio (2025)
The purpose of the study was to explain how reflective feedback influences the development of critical thinking skills in students from the School of International Business and Tourism at the National University of the Peruvian Amazon, in Iquitos, during 2024. This was an explanatory research study with a bivariate, cross-sectional, and field design, adopting a quantitative, non experimental approach. The sample consisted of 449 university students, who administered a survey composed of a questionnaire and a written case test, both validated by experts. Reflective teacher feedback was explained through the results of simple regression analysis, which showed a significant positive influence on the development of critical thinking skills. The linear regression analysis revealed that reflective feedback accounted for 47.9% of the variability in critical thinking skills (R² = .479). This finding highlights the importance of strengthening reflective feedback in pedagogical practices to foster greater development of critical thinking in students.